1980
DOI: 10.1126/science.7188647
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-Egg Interaction: Evidence for Boar Sperm Plasma Membrane Receptors for Porcine Zona Pellucida

Abstract: Freshly ejaculated, noncapacitated boar sperm bind rapidly and in large numbers to pig egg zona pellucida in vitro. In the present study, the number of sperm bound decreased sharply when sperm motility was lowered by energy poisons or by reducing the temperature. Highly motile sperm from humans, guinea pigs, and rats, added at concentrations ten times higher than control sperm, did not bind to the porcine zona. At the same high concentration, a small number of hamster and bull sperm bound to the zona. Binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1

Year Published

1981
1981
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(27 citation statements)
references
References 11 publications
1
25
1
Order By: Relevance
“…However, it was clearly shown in the present study that incubation of pig spermatozoa in the presence of DFM-H, Swainsonine or galactal, the inhibitors of α-Lfucosidase, α-D-mannosidase and β-Dgalactosidase, respectively, did not affect sperm motility but greatly reduced the number of spermatozoa bound to the ZP. Although it has been reported that pig spermatozoa which initially bind to the ZP have intact plasma membrane [30][31][32], the present results indicate that, in the pig, only spermatozoa undergoing or completing acrosome reaction could bind firmly to the ZP as suggested by Jones et al [33]. However, it is unclear at present how α-L-fucosidase might be involved in binding of spermatozoa to the ZP because it has been shown that fucose residues are present only in the inner region of the ZP [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was clearly shown in the present study that incubation of pig spermatozoa in the presence of DFM-H, Swainsonine or galactal, the inhibitors of α-Lfucosidase, α-D-mannosidase and β-Dgalactosidase, respectively, did not affect sperm motility but greatly reduced the number of spermatozoa bound to the ZP. Although it has been reported that pig spermatozoa which initially bind to the ZP have intact plasma membrane [30][31][32], the present results indicate that, in the pig, only spermatozoa undergoing or completing acrosome reaction could bind firmly to the ZP as suggested by Jones et al [33]. However, it is unclear at present how α-L-fucosidase might be involved in binding of spermatozoa to the ZP because it has been shown that fucose residues are present only in the inner region of the ZP [23].…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that species specificity in gamete interaction is determined by components on the surface of the sperm plasma membrane and that of the zona pellucida (Peterson, Russell, Bundman & Freund, 1979, 1980. The membrane components involved in gamete recognition have been identified in several species.…”
Section: Introductionmentioning
confidence: 99%
“…Ligand-like elements were demonstrated on boar spermatozoa by the use of antiserum and univalent (Fab) antibody (Peterson et al, 1979(Peterson et al, ,1980. Sugar treatment of mouse (Chapman, Lambert & Le, 1982 ; and hamster (Ahuja, 1982) (West, Freís, Papaioannous, Karr & Chapman, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…However, this assumes that prematurely bound sperm are engaged in a productive binding-that is, an interaction which leads to penetration. Such an assumption is not necessarily justified because a number of sperm-zona binding reactions shown by ourselves and others do not necessarily lead to penetration (6,20).…”
Section: Discussionmentioning
confidence: 97%
“…The mammalian egg consists of an egg cell proper (or vitellus) surrounded by the zona pellucida, an acellular envelope composed largely of glycoproteins (1-4). The zona possesses species-specific binding sites for sperm (5,6) and is a barrier to multiple sperm penetration in most of the species studied (7,8). In both the hamster and the mouse, it has recently been shown that the sperm bind to the surface of the zona pellucida by means of the plasma membrane of the sperm head (9)(10)(11).…”
mentioning
confidence: 99%